Polski reportaż literacki w perspektywie międzykulturowej. Z zagadnień recepcji gatunku - Frukacz, Katarzyna (Studia Europaea Gnesnensia, 2016)
The article aims to determine how the genre of literary reportage is perceived in various target cultures. The analysis takes into account the findings of a survey conducted in Russia, Germany and the Czech Republic. The paper also outlines the standing of reportage writing in the literary tradition of those countries.